The incidence of congenital syphilis in the municipality of Itumbiara, Goiás, from 2015 to 2020: possible impacts of the pandemic caused by SARS-CoV-2 (Research, Society and Development, 2022)
Introduction: vertical transmission of syphilis occurs during pregnancy, by untreated or inadequately treated women. The consequences for the newborn are serious: prematurity, stillbirth and manifestations such as deafness, blindness, mental deficiency, bone and even dental alterations. According to the World Health Organization (WHO), each year there would be approximately 1.5 million cases of syphilis in pregnant women. Objective: to know the incidence of syphilis in the municipality of Itumbiara (GO) from 2015 to 2020 and its relationship with the COVID-19 pandemic, as well as to investigate cases and detection rate of congenital syphilis in the municipality of Itumbiara (GO) in period from 2015 to 2020, in relation to age, sex, age group of the mother, among others, and to analyze the influence of the pandemic on the number of cases of congenital syphilis in the municipality of Itumbiara (GO), with comparative data from 2015 to 2020. Methodology: this is an epidemiological study, with a quantitative approach, of an exploratory and descriptive nature, with retrospective data based on the database of the Notifiable Diseases Information System (SINAN). Results and discussion: Of the 279 women diagnosed with syphilis, 213 were pregnant (about 76.3%), the year with the most diagnoses was 2017 (21.6%) and the lowest was 2018 (9.4%), with fewer cases than in the first half of 2020. The highest detection rate of the disease in pregnant women was in 2016 (31.8). Furthermore, in terms of treatment, most cases of gestational syphilis were treated with penicillin both at all times (95.5%) and annually. The year 2019 was the year with the lowest percentage of penicillin use (84.6%). Of the 13 cases of congenital syphilis, 8 of them (61.5%) had prenatal care during pregnancy, while 5 (38.5%) did not. Final considerations: the study performed a dynamic diagnosis on the occurrence of congenital syphilis cases through the ratio of the number of cases between the year 2015 to 2020. These collected subsidies may provide explanations about the number of cases of congenital syphilis in the municipality, they may also contribute to the identification of the epidemiological reality of the municipality in relation to the diagnosis, treatment and prevention of congenital syphilis.